2020
DOI: 10.3390/su12229539
|View full text |Cite
|
Sign up to set email alerts
|

Factors Driving Success of Cost Management Practices in Integrated Project Delivery (IPD)

Abstract: Integrated project delivery (IPD) is a mode of project procurement recognised as facilitating superior project performance. However, this success is contingent on effective cost management practices that share cost data with all project stakeholders in an accurate, timely and transparent manner. Despite an extensive literature on aspects of cost management, none identifies the essential ingredients required of an effective cost management system, sufficiently robust to support successful IPD projects. Candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…IPD projects were seen to lack any accurate cost estimation methodology at the front-end of projects (Elghaish et al , 2019) and fair profit distribution (Teng et al , 2019) was identified as the key weakness in IPD cost management (Elghaish and Abrishami, 2020a). Discussion of IPD’s cost management deficiency invoked integration of several concepts (Elghaish et al , 2020b). By way of defense, Love et al (2017) argued that cost certainty improved when BIM was coupled with IPD.…”
Section: Resultsmentioning
confidence: 99%
“…IPD projects were seen to lack any accurate cost estimation methodology at the front-end of projects (Elghaish et al , 2019) and fair profit distribution (Teng et al , 2019) was identified as the key weakness in IPD cost management (Elghaish and Abrishami, 2020a). Discussion of IPD’s cost management deficiency invoked integration of several concepts (Elghaish et al , 2020b). By way of defense, Love et al (2017) argued that cost certainty improved when BIM was coupled with IPD.…”
Section: Resultsmentioning
confidence: 99%
“…By prioritizing the perspectives and voices of these actors, new concepts and insights can emerge throughout the entire research process, including data collection, analysis, and the reporting of findings [44]. While there are studies that approach this topic through methods such as systematic literature review [45,46], case studies [10], and surveys [47], a qualitative approach centred around multidisciplinary experts view is rather a less-explored, particularly in an Australian context.…”
Section: Methodsmentioning
confidence: 99%
“…[47] 1. The critical success factors of cost management practices to facilitate Integrated project delivery (IPD); 2.…”
mentioning
confidence: 99%
“…In the case of conventional PDMs, contractors and manufacturers are involved in the project after the project's design phase. Thereby, traditional construction processes tend to incur more costs from rework resulting from miscoordination, quality issues, the inefficiency of project delivery times, poor performance, and client dissatisfaction with the product delivered [44].…”
Section: Integrated Project Delivery (Ipd)mentioning
confidence: 99%